A Review on Barber Shop Service Booking App (International Journal of Scientific Research in Science and Technology, 2025)
Time is the most precious thing. People need barber’s service for looking good and clean. A person would like to get his turn for the haircut as soon as he reaches the barber but unfortunately that rarely happen. People don’t get their turn for haircut as they reach the salon because some number of people are already waiting there at the salon for their turn. There is no way to know how many customers are already waiting at the salon so a lot of time & energy is wasted in this scenario. In this busy world where time is short for everything, we need to make best use of our time and manage it optimally. People have to wait for their turn when they go to hair salon & a lot of time is wasted there in the waiting line. We can solve this problem by providing a modern solution where people can simply book or enquire (see the current number of waiting customers) about their favourite salon using a user-friendly app.
Keywords: Barber; app; salon; time; efficiency